Carbohydrate Intake in Non-communicable Disease Prevention and Treatment - Venn, Bernard (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
In 2011, carbohydrates provided 63% of the dietary energy intake to the world’s population. Historically, carbohydrate-rich diets have been associated with good health and longevity but there has been a move away from traditional carbohydrate-rich diets, with refined carbohydrate taking much criticism for contributing to non-communicable disease. The aim of this Special Issue is to discuss the appropriate use of environmentally sustainable carbohydrate-rich foods in the modern diet in developing and developed countries in the context of prevention and treatment of non-communicable disease.